The inter-banking automatic teller machines use (ATMS): Its legal challenges in Tanzania. - Mwetindwa, Asha.H. (Mzumbe University, 2024)
A dissertation submitted to Mzumbe University as a partial fulfillment of the requirement for the award of Master’s Degree of Laws in Commercial Laws (LL.M. CL) of Mzumbe University